Optimalisasi Peran Pelaut Indonesia di Belanda sebagai Bagian Perwujudan Indonesia Menjadi Poros Maritim Dunia - Hidayat, Novan Wahyu; Setiawan, Titus Hari; Haris Padilah; Haryani (Majalah Ilmiah Gema Maritim, 2024)
Indonesian Seafarers have a crucial role in helping to develop the country and supporting the sustainability of Indonesia as the World Maritime Axis. This scientific writing aims to discover and explain the role of Indonesian Seafarers in the Netherlands as part of Indonesia's realization of becoming the world's maritime axis. The research method that has been carried out is using a descriptive qualitative approach, and in collecting data, apart from documents, researchers also need research subjects such as related agencies and several Indonesian Seafarers who work on Dutch ships, and means of literature studies and field studies carried out data analysis. From the results of the discussion, it was found that 1) to realize Indonesia as the world's maritime axis, competent Human Resources (HR) must be available in sufficient numbers, 2) The shipping industry in the Netherlands is one of the most varied in the world because it employs thousands of seafarers Indonesia, 3) Maritime educational institutions in Indonesia must be able to improve the quality of the learning process and be able to create a link and match program between the campus and the world of work so that qualifications and educational quality standards can be achieved. From this study, it can be concluded that to realize Indonesia as the world's maritime axis and optimize the role of Indonesian Seafarers on the international stage, it is mandatory to master English and have adequate hard and soft skills to compete well.